Knowledge of General Practitioner Doctors and Midwives Who Has and Has Not Attended Neonatal Resuscitation Course Has No Significant Difference - Vincent Geraldus Enoch Lusida; Bambang Pujo Semedi; Bambang Herwanto (Indonesian Journal of Anesthesiology and Reanimation, 2019)
Introduction: Infant death is most prominent in the neonatal period. The success of neonatal resuscitation practice has many contributing factors. One of which is the health workers' knowledge of the Neonatal Resuscitation Program (NRP) algorithm. Therefore, it is necessary to conduct studies to evaluate the health workers' knowledge of the Neonatal Resuscitation Program who are educated in neonatal resuscitation course and has taken part in Neonatal Life Support practice in primary health care (PHC)  Objective: This study aims to analyze the knowledge of general practitioners and midwives who has or has not attended in neonatal resuscitation course in Surabaya PHC Methods and Materials: this research is descriptive, cross-sectional research. All Basic Emergency Obstetric and Newborn Care (BEmONC) PHC in Surabaya which are Jagir PHC, Banyu Urip PHC, Medokan Ayu PHC, Tanah kali Kedinding PHC, Tanjungsari PHC, Balongsari PHC, Sememi PHC, Simomulyo PHC is included in this research from 2018 to 2019. A nine-item questionnaire referenced from The Textbook of Neonatal Resuscitation 7th Edition is given to ten respondents in each BEmONC PHC. Results and Discussion: from the total sample of 78 respondents, 32 (41,0%) receive a high score, 20 (25,7%) receive a middle score, and 26 (33,3%) receive a low score. The data shows that there is no significant score difference between respondents who has or has not participate in the NRP course (p=0,419). Conclusion:  There is no correlation between difference knowledge midwives and general practitioners who had and had not attended neonatal resuscitation training at basic emergency obstetric and newborn care in public health center Surabaya.